(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
The behavior of anods consisting Pb–0,8% Ag and Pb–6,3% Sb alloys in sulphuric acid leaching solution of calcinning copper concentrate has been investigated. The influence of the technological factors of copper electrowinning on the anodic processes and the purity of cathodic deposition has been shown.